Synergistic regulation of Notch signaling by different O-glycans promotes hematopoiesis - Tanwar, Ankit; Stanley, Pamela (Frontiers in Immunology, 2023)
Glycosylation of Notch receptors by O-fucose glycans regulates Notch ligand binding and Notch signaling during hematopoiesis. However, roles in hematopoiesis for other O-glycans that modify Notch receptors have not been determined. Here we show that the EGF domain specific GlcNAc transferase EOGT is required in mice for the optimal production of lymphoid and myeloid cells. The phenotype of Eogt null mice was largely cell-autonomous, and Notch target gene expression was reduced in T cell progenitors. Moreover, EOGT supported residual Notch signaling following conditional deletion of Pofut1 in hematopoietic stem cells (HSC). Eogt:Pofut1 double mutant HSC had more severe defects in bone marrow and in T and B cell development in thymus and spleen, compared to deletion of Pofut1 alone. The combined results show that EOGT and O-GlcNAc glycans are required for optimal hematopoiesis and T and B cell development, and that they act synergistically with POFUT1 and O-fucose glycans to promote Notch signaling in lymphoid and myeloid differentiation.